Management of pregnancy in women with cancer. Issue 3 (March 2021) - Wolters, Vera; Heimovaara, Joosje; Maggen, Charlotte; Cardonick, Elyce; Boere, Ingrid; Lenaerts, Liesbeth; Amant, Frédéric
Abstract : As the incidence of cancer in pregnancy has been increasing in recent decades, more specialists are confronted with a complex oncologic–obstetric decision-making process. With the establishment of (inter)national registries, including the International Network on Cancer, Infertility and Pregnancy, and an increasing number of smaller cohort studies, more evidence on the management of cancer during pregnancy is available. As fetal, neonatal, and short-term pediatric outcomes after cancer treatment are reassuring, more women receive treatment during pregnancy. Prenatal treatment should adhere to standard treatment as much as possible to optimize maternal prognosis, always taking into account fetal well-being. In order to guarantee the optimal treatment for both mother and child, a multidisciplinary team of specialists with expertise should be involved. Apart from oncologic treatment, a well-considered obstetric and perinatal management plan discussed with the future parents is crucial. Results of non-invasive prenatal testing are inconclusive in women with cancer and alternatives for prenatal anomaly screening should be used. Especially in women treated with chemotherapy, serial ultrasounds are strongly recommended to follow-up fetal growth and cervical length. After birth, a neonatal assessment allows the identification of any cancer or treatment-related adverse events. In addition, placental histologic examination aims to assess the fetal risk of metastasis, especially in women with malignant melanoma or metastatic disease. Breastfeeding is discouraged when systemic treatment needs to be continued after birth. At least a 3-week interval between the last treatment and nursing is recommended to prevent any treatment-induced neonatal effects from most non-platinum chemotherapeutic agents.